Korelasi antara Status Gizi Pranikah dan Perencanaan Kehamilan Calon Pengantin - Nur - Khafidhoh; Fina Nurul Azizah (Midwifery Department, Poltekkes Kemenkes Denpasar, Indonesia, 2025)
The premarital period is closely related to the preconception period because after marriage, women will undergo fertilization activities. Entering the preconception period means preparing to become a mother. Pregnancy planning is important to motivate behavior change before and during pregnancy. According to WHO, 4 out of 10 pregnant women did not plan their pregnancies, leading to delayed interventions. The 2019 Indonesian Ministry of Health survey reported a Maternal Mortality Rate (MMR) of 305 per 100.0000 live births and anemia prevalence of 48.9% among pregnant women. These issues highlight the need for prospective brides to plan pregnancies before marriage. However, awareness of preconception care remains low, with most care starting only before delivery. This study aimed to determine the relationship between premarital nutritional status and pregnancy planning. A quantitative cross-sectional study was conducted among 150 brides visiting health centers in the Kendal district, using accidental sampling. Data were analyzed with the Chi-Square test. Results showed a significant relationship between hemoglobin levels and pregnancy planning (p = 0.005), but no relationship between Body Mass Index (BMI) and Mid Upper Arm Circumference (MUAC) with pregnancy planning. The study concludes that improving education on preconception nutritional status for brides-to-be is essential to enhance pregnancy readiness and outcomes.